Continuous versus discontinuous drinking of an ethanol liquid diet in peripubertal rats: Effect on 24-h variation of lymph node and splenic mitogenic responses and lymphocyte subset populations - Jiménez Ortega, Vanesa (2011)
Excessive alcohol consumption continues to be a major public health problem, particularly in the adolescent and young adult populations. Generally, such a behavior tends to be confined to the weekends, to attain frequently binge drinking. This study in peripubertal male rats compares the effect of the discontinuous feeding of a liquid diet containing a moderate amount of ethanol (6.2% wt/vol) to that of continuous ethanol administration or a control diet, taking as end points the 24-h variations of plasma prolactin levels and mitogenic responses and lymphocyte subset populations in submaxillary lymph nodes and spleen. Animals received the ethanol liquid diet starting on day 35 of life, the diet being similar to that given to controls except for that maltose was isocalorically replaced by ethanol. Ethanol provided 36% of the total caloric content. Every week, the discontinuous ethanol group received the ethanol diet for 3 days and the control liquid diet for the remaining 4 days. After 4 weeks, rats were killed at six time intervals, beginning at 0900h. A significant decrease of splenic cells' response to concanavalin A, and of lymph node and splenic cells' response to lipopolysaccharide was found in rats under the discontinuous ethanol regime, when compared with control- or ethanol-chronic rats. Under discontinuous ethanol feeding, mean values of lymph node and splenic CD8+ and CD4+-CD8+cells decreased, whereas those of lymph node and splenic T cells, and splenic B cells, augmented. In rats chronically fed with ethanol, splenic mean levels of CD8+ and CD4+-CD8+cells augmented. Both modalities of ethanol administration disrupted the 24h variation in immune function seen in controls. Mean plasma prolactin levels increased by 3.6-fold and 8.5-fold in rats chronically or discontinuously fed with alcohol, respectively. The immune parameters examined in an additional group of rats fed regular chow and water ad libitum did not differ significantly from control liquid diet. The results support the view that the discontinuous drinking of a moderate amount of ethanol can be more harmful for the immune system than a continuous ethanol intake, presumably by inducing a greater stress as indicated by the augmented plasma prolactin levels observed.